Ahmad Wahib and the Academic Struggle in Indonesia's Multicultural Society - Ahmad Nabil Amir; Tasnim Abdul Rahman (Pascasarjana IAIN Metro, 2025)
The paper reviews Ahmad Wahib’s (1942-1973) underlying ideas on religion and its present experience in contemporary Indonesia. A young proponent of rational understanding of Islam and society, he stands out as leading advocate of humanistic approach as enshrined in his activism in HMI that projected rational, holistic, existential and sympathetic understanding of Islam. His work highlighted religious issues of pluralistic nature, in defining the contours of Indonesian society. The method of study is based on qualitative survey in the form of library and documentative technique. It traces the historical work of Ahmad Wahib and the corresponding literature in the field. This was analyzed using descriptive, analytical and historical method to interpreted and concluded his idealism and struggle. The study found that Ahmad Wahib had developed in-depth philosophical viewpoint of Islam based on contextual understanding of its sources, outlining his response and insight on issues pertaining to moral, spiritual and intellectual implication of religious postulate in society, emphasizing its role to drive modern cultural and ethical renewal based on its balance theoretical principle which offers ideal interpretation of the socio-political condition and future direction in Indonesia.